Research methodology : a step-by-step guide for beginners - Kumar, Ranjit (SAGE, 2014)
This text has been written specifically for those with no previous experience of research or research methodology. Written in a logical and accessible style and providing helpful techniques and examples, it breaks the process of designing and doing a research project into eight manageable operational steps. The book guides you through your project from beginning to end by offering practical advice on: formulating a research question ; ethical considerations ; carrying out a literature review ; choosing a research design ; selecting a sample ; collecting and analysing qualitative and quantitative data ; writing a research report. The book is essential reading for undergraduate and postgraduate students in the social sciences embarking on quantitative or qualitative research projects.